Estimation of genetic diversity in sweet pepper (Capsicum annuum L.) through multivariate analysis (Journal of the Sylhet Agricultural University, 2025)
Sweet pepper is an important emerging exotic vegetable crop in Bangladesh, which play an essential function in the country economy, food and nutrition but there are not enough acceptable high yielding varieties. In this regard the objectives of this investigation was to ascertain the extent of genetic variation and to mark out the diverse parents among the genotypes that was collected for the purpose of implementing a hybridization program. Twenty one genotyes were employed and the analysis of variance (ANOVA) demonstrated that the genotypes exhibited significant (p